(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Exercise tolerance test (ETT) is a well-known available and affordable noninvasive investigation for evaluation of CAD. But equivocal result create dilemma in their treatment strategy. Objective of the present study was to find the different angiographic pattern among the equivocal ETT patients. Methods This is an observational study was done at, Ibrahim Cardiac Hospital & Research Institute from January 2018 to September 2018. 44 patients with equivocal ETT findings undergoing coronary angiogram were included. Clinical & angiographic findings were statistically analyzed. Results During study period 1888 individuals were underwent ETT. Among them 308 (16.31%) patients had equivocal ETT. Only 44 (14.3%) of them underwent CAG. Male & female were equal. Angiographic study revealed 75% patients had normal & non-critical coronary arteries, significant single & double vessel involvements were 18.8% &6.82% respectively. There were no patients who had triple vessel disease. Conclusion Obstructive CAD was found in one in five ‘‘equivocal” ETT. Severe Triple vessel disease or Left main CAD diseases were not found in CAG findings of ‘‘equivocal” ETT patients. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 264-267